Global burden and attributable risk factors of acute lymphoblastic leukemia in 204 countries and territories in 1990–2019: Estimation based on Global Burden of Disease Study 2019. Issue 1 (24th October 2021) - Hu, Yuefen; Zhang, Xiuping; Zhang, Aijun; Hou, Yu; Liu, Yang; Li, Qizhao; Wang, Yawen; Yu, Yafei; Hou, Ming; Peng, Jun; Yang, Xiaorong; Xu, Shuqian
Abstract: To provide a foundational guideline for policy‐makers to efficiently allocate medical resources in the context of population aging and growth, the latest spatial distribution and temporal trend of acute lymphoblastic leukemia (ALL) along with attributable risk factors by sex and age were mapped. Based on the Global Burden of Disease Study 2019, estimated annual percentage change (EAPC) was calculated according to the relativity between age‐standardized rate and calendar year, to quantify temporal trends in morbidity and mortality of ALL. We used applied Spearman rank correlation to estimate the relationship between the EAPC and potential influence factors. The population attributable fraction of potential risk factors for ALL‐related disability‐adjusted life years were estimated by the comparative risk assessment framework. As a result, we found that new ALL cases increased significantly by 1.29% worldwide, and the age‐standardized incidence rate increased by 1.61% annually. The proportion of elder patients sharply increased, especially within the higher socio‐demographic index (SDI) region. Smoking and high body mass index remained the predominant risk factors for ALL‐related mortality. Notably, the contribution of high body mass index presented an increasing trend. In conclusion, the global burden of ALL has steadily increased, especially in Middle SDI region. Health measures and new drugs should be taken into consideration to improve the management and treatment of elders with ALL due to an increasing proportion in the higher SDI region. For Low SDI areas, attention should be paid to the environmental problems caused by industrial development.